Molecular and Clinical Characterization of PD-1 in Breast Cancer Using Large-Scale Transcriptome Data - Liu, Qiang; Cheng, Ran; Kong, Xiangyi; Wang, Zhongzhao; Fang, Yi; Wang, Jing (Frontiers in Immunology, 2020)
Despite the impressive impact of programmed cell death protein 1(PD-1)-targeted cancer immunotherapy, a large proportion of cancer patients fail to respond. The impact of PD-1 on immune cells other than T cells and the synergistic role of PD-1 with other immune modulators remain largely unknown. To fill this gap, we systematically investigated PD-1-related transcriptome data and relevant clinical information derived from a total of 2994 breast cancer patients recorded in The Cancer Genome Atlas (TCGA) and Molecular Taxonomy of Breast Cancer International Consortium (METABRIC). Our results revealed the relationship between PD-1 and major molecular and clinical characteristics in breast cancer. More importantly, we depicted the association landscape between PD-1 and other immune cell populations. Gene ontology analyses and Gene Set Variation Analysis (GSVA) of genes correlated with PD-1 revealed that PD-1was mainly involved in immune responses and inflammatory activities. We also elucidated the association of PD-1 with other immune modulators in pan-cancer level, especially the potential synergistic relationship between PD-1 and other immune checkpoints members in breast cancer. In short, PD-1 expression was closely related to breast cancer malignancy and might serve as a potential biomarker; PD-1 might manipulate the anti-tumor immune response by impacting not only T cells but also other immune cells, and this might vary with different tumors. Furthermore, PD-1 might synergize with other immune checkpoint members to modulate the immune microenvironment in breast cancer. To the best of our knowledge, this is by far the most comprehensive and largest study characterizing the molecular and clinical features of PD-1 in breast cancer using large-scale transcriptome data.